2016
DOI: 10.1002/jmcd.12051
|View full text |Cite
|
Sign up to set email alerts
|

A Content Analysis of Research on Disability: American Counseling Association Journals Between 2003 and 2013

Abstract: This content analysis provides an overview of disability articles published in 10 major American Counseling Association journals between 2003 and 2013. In addition to the number of disability articles published during this time period, other content areas such as authorship and institutional contributors; methodology, location, and application settings; target populations and sample characteristics; type of disabilities; and topics of interest are identified. Recommendations for counseling scholars to increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 41 publications
1
14
0
2
Order By: Relevance
“…In terms of authorship and institutional affiliations, the majority of the articles were written by two or more authors, which is similar to the findings of previous content analyses (e.g., Woo et al 2016 ; Woo & Neo, 2013 ). Also, like many other content analyses in counseling (e.g., Erford et al 2011 ; Woo & Neo, 2013 ), we found that most of the leading authors of the studies analyzed were affiliated with universities/colleges, while only a few were counseling practitioners affiliated with private counseling clinics.…”
Section: Discussionsupporting
confidence: 84%
“…In terms of authorship and institutional affiliations, the majority of the articles were written by two or more authors, which is similar to the findings of previous content analyses (e.g., Woo et al 2016 ; Woo & Neo, 2013 ). Also, like many other content analyses in counseling (e.g., Erford et al 2011 ; Woo & Neo, 2013 ), we found that most of the leading authors of the studies analyzed were affiliated with universities/colleges, while only a few were counseling practitioners affiliated with private counseling clinics.…”
Section: Discussionsupporting
confidence: 84%
“…To examine what the counseling profession has published on GC, as well as to prepare the profession to work with the growing number of older adult clients, we completed a 26‐year content analysis of GC scholarship. In recent years, several content analyses have emerged to examine and highlight critical issues facing the counseling profession, including male clients in counseling (Evans, 2013), traumatology (Webber, Kitzinger, Runte, Smith, & Mascari, 2017), multiculturalism (Arredondo, Rosen, Rice, Perez, & Tovar‐Gamero, 2005), counseling leadership (McKibben, Umstead, & Borders, 2017), social class (Clark, Cook, Nair, & Wojcik, 2018), disability (Woo, Goo, & Lee, 2016), and LGBTQ+ issues in qualitative research (Singh & Shelton, 2011). In light of a perceived dearth of research on older adults across journals in the counseling profession, an examination of conceptual and empirical research serves as a useful tool to locate gaps in the counseling profession and opportunities.…”
Section: Purpose Of the Content Analysismentioning
confidence: 99%
“…To date, no content analysis has specifically targeted GC across journals in the counseling profession. Moreover, although previous content analyses on non‐GC topics have certainly contributed to the counseling profession’s body of knowledge, their scope has typically been limited to less than 20 years’ worth of data (e.g., Clark et al, 2018; Woo et al, 2016) or focused on only a small set of journals (e.g., Arredondo et al, 2005; Singh & Shelton, 2011; Webber et al, 2017).…”
Section: Purpose Of the Content Analysismentioning
confidence: 99%
“…Furthermore, according to a study published by the Centers for Disease Control and Prevention (Courtney‐Long et al, ), one in five, or about 53 million, adults have a physical, sensory, psychiatric, or cognitive disability that interferes with daily living. Individuals with disabilities (IWDs) encounter a multitude of issues, including developmental tasks, adjustment to a disability, career aspirations and transitions, advocacy, quality of life, and cultural identity (Woo, Goo, & Lee, ), and are at an increased risk for lower subjective well‐being than individuals without disabilities (Emerson, Llewellyn, Honey, & Kariuki, ; Okoro & Dhingra, ). Additionally, their caregivers are more likely to experience depression, chronic stress, frustration, and lower levels of psychological well‐being (Schulz & Sherwood, ).…”
mentioning
confidence: 99%
“…With regard to an individual, disability is defined as (a) a physical or mental impairment that substantially limits one or more major life activities, (b) a record of such an impairment, or (c) being regarded as having such an impairment (Americans With Disabilities Act [ADA], 1990; ADA Amendments Act, 2008). Disability is one aspect of diversity that has frequently been overlooked by the counseling profession (Woo et al, ), even though leaders in the field (e.g., Ratts, Singh, Nassar‐McMillan, Butler, & McCullough, ; Sue, Arredondo, & McDavis, ) and counseling organizations (e.g., American Counseling Association [ACA], ; American School Counselor Association [ASCA], ; Association for Multicultural Counseling and Development [AMCD], Sue et al, ; Council for Accreditation of Counseling and Related Educational Programs [CACREP], ) have promoted multicultural sensitivity, knowledge, and skills. Overall, counselors must demonstrate competence and ability to provide adequate counseling services (ACA, ; CACREP, ).…”
mentioning
confidence: 99%